Natural areas as a basis for assessing ecosystem vulnerability to climate change. Issue 11 (18th November 2016) - H. Massie, Margaret; Wilson, Todd M.; Morzillo, Anita T.; Henderson, Emilie B.
Abstract: There are more than 580 natural areas in Oregon and Washington managed by 20 federal, state, local, and private agencies and organizations. This natural areas network is unparalleled in its representation of the diverse ecosystems found in the Pacific Northwest, and could prove useful for monitoring long‐term ecological responses to climate change. Our objectives were to (1) evaluate potential effects of climate change on these natural areas and (2) develop strategies for selecting and prioritizing sites for long‐term monitoring. Bioclimatic and Random Forest modeling were used to identify subsets of natural areas to prioritize for long‐term monitoring efforts based on the current and projected (2020s, 2050s, 2080s) outputs from 13 future climate models. Projection consensus suggest some of the largest effects of climate change on natural areas may be the result of a substantial range increase in suitable climate for warmer‐adapted forest types coupled with a reduction in habitat for cooler‐adapted forest types. We identify four strategies that could be used for prioritizing sites and help manage and protect biodiversity in the Pacific Northwest, especially given uncertainty over climate change effects.